2020
DOI: 10.5194/cp-16-2275-2020
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the coupled atmosphere–ocean–sea ice–vegetation model COSMOS to the PlioMIP2

Abstract: Abstract. We present the Alfred Wegener Institute's contribution to the Pliocene Model Intercomparison Project Phase 2 (PlioMIP2) wherein we employ the Community Earth System Models (COSMOS) that include a dynamic vegetation scheme. This work builds on our contribution to Phase 1 of the Pliocene Model Intercomparison Project (PlioMIP1) wherein we employed the same model without dynamic vegetation. Our input to the PlioMIP2 special issue of Climate of the Past is twofold. In an accompanying paper we compare res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 87 publications
(274 reference statements)
8
36
0
Order By: Relevance
“…Model results show that during KM5c the Mediterranean experienced 2-3°C warmer temperatures, shifting its hydrological balance into greater net loss of freshwater 46 . This is a similar climate development as predicted for the Mediterranean region until the year 2100 47,48 . Consequently, the lack of freshwater influx to the Mediterranean during KM5c probably boosted its salinities and with it MOW production (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Model results show that during KM5c the Mediterranean experienced 2-3°C warmer temperatures, shifting its hydrological balance into greater net loss of freshwater 46 . This is a similar climate development as predicted for the Mediterranean region until the year 2100 47,48 . Consequently, the lack of freshwater influx to the Mediterranean during KM5c probably boosted its salinities and with it MOW production (Fig.…”
Section: Resultssupporting
confidence: 82%
“…The ocean model MPI‐OM (Marsland et al., 2003), including sea‐ice dynamics formulated using viscous‐plastic rheology (Hibler III, 1979), has a resolution of GR30 (3° × 1.8°) in the horizontal, with 40 uneven vertical layers. COSMOS has previously been used to investigate a range of paleoclimate phenomena, including the last millennium (Jungclaus et al., 2010), the Miocene warm climate (Hossain et al., 2020; Knorr & Lohmann, 2014), the Pliocene (Stepanek et al., 2020), internal variability of the climate system (Wei et al., 2012), Holocene variability (Wei & Lohmann, 2012), the Last Glacial Maximum (LGM) climate (Abelmann et al., 2015; Zhang et al., 2013) and glacial millennial‐scale variability (Gong et al., 2013; Maier et al., 2018; Zhang et al., 2014, 2017). This indicates that it is capable of capturing key features of different climate states and is thus a suitable climate model for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The mPWP is often used as an analogue for near-future climate change due to its similar-to-modern paleogeography and high concentrations of CO 2 in the atmosphere (Corvec and Fletcher, 2017;Dowsett et al, 2013;Sun et al, 2013), and both marine and terrestrial proxy reconstructions indicate a climate with higher sea surface and surface air temperatures than present (Dowsett et al, 2013;Salzmann et al, 2008). A model-data comparison using PlioMIP1 indicated that the models underestimated the high-latitude warming by up to 15 • C, while overestimating the low-latitude temperatures by 1-6 • C (Dowsett et al, 2013;Haywood et al, 2013;Salzmann et al, 2013).…”
Section: The Paleo-proxy Evidence For Wam During the Mid-pliocenementioning
confidence: 99%